Group A Streptococcal Panniculitis. Issue 2 (1st August 2012) - Villaseñor‐Park, Jennifer; Davis, Amy; Singh, Sonia; Zuckerbraun, Noel; Green, Michael; Gehris, Robin
Abstract Infectious panniculitis caused by group A beta‐hemolytic streptococcus is rare, especially in immunocompetent patients. Its clinical presentation is usually nonspecific, but skin biopsy may provide information on the source. We describe the case of a previously healthy 2‐year‐old girl who presented with fever, tachycardia, and diffuse erythematous skin nodule; biopsy revealed a deep lobular neutrophilic panniculitis with gram‐positive bacteria.